A randomized trial of teriflunomide added to glatiramer acetate in relapsing multiple sclerosis. (3rd December 2015) - Freedman, MS; Wolinsky, JS; Truffinet, P; Comi, G; Kappos, L; Miller, AE; Olsson, TP; Benamor, M; Chambers, S; O'Connor, PW
Background: Teriflunomide is a once-daily oral immunomodulator for the treatment of relapsing−remitting MS. Objective: To evaluate the safety and tolerability of teriflunomide as add-on therapy to a stable dose of glatiramer acetate (GA) in patients with relapsing forms of MS (RMS). Methods: Phase II, randomized, double-blind, add-on, placebo-controlled study. The primary objective was to assess safety and tolerability; secondary objectives were to evaluate effects of treatment on disease activity assessed by MRI and relapse. Results: Patients with RMS on GA ( N = 123) were randomized 1:1:1 to receive teriflunomide 14 mg ( n = 40), 7 mg ( n = 42), or placebo ( n = 41) for 24 weeks; 96 patients entered the 24-week extension, remaining on original treatment allocation. Teriflunomide was well tolerated over 48 weeks. The frequency of adverse events (AEs) was low across all groups; 5 (12.2%), 3 (7.1%), and 2 (5.0%) patients in the 14 mg, 7 mg, and placebo groups, respectively, discontinued treatment due to AEs. Teriflunomide reduced the number of T1-Gd lesions vs placebo (14 mg: 46.6% relative reduction, p = 0.1931; 7 mg: 64.0%: relative reduction, p = 0.0306). Conclusions: Teriflunomide added to stable-dose GA had acceptable safety and tolerability, and reduced some MRI markers of disease activity compared with GA alone. NCT00475865 (core study); NCT00811395 (extension).